Optimized AIS-Derived Indicators through Application of Port Administrative Boundaries - Nastiar, Gery; Pramana, Setia; Krismawati, Dewi (Sekretariat Badan Kebijakan Transportasi, Formerly by Puslitbang Transportasi Laut, Sungai, Danau, dan Penyeberangan, 2025)
Defining port boundaries for Automatic Identification System (AIS) data processing is challenging, since docks and berthing facilities are relatively easy to define, while anchorage zones in open waters are often less clearly delineated. This study uses administrative boundaries, known as Daerah Lingkungan Kerja Pelabuhan (Port Working Area, DLKr), to represent port areas as the Area of Interest (AoI) in AIS data processing. With DLKr, port boundaries can be clearly outlined and divided into several zones, enabling more accurate calculation of AIS-derived indicators. The research estimates port calls and port stay durations using the Stationary Marine Broadcast Method (SMBM), focusing on cargo, tanker, and passenger vessels at the Port of Tanjung Priok during 2024. The AIS-derived indicators generated with DLKr as the AoI show good performance, with an RMSE of 55.94 and a MAPE of 5.27%. In addition, the results are supported by the similarity in patterns and distribution of port call values when compared with the official maritime statistics provided by the Ministry of Transportation.